Instructors manual to accompany statistics for business and economics / David R. Anderson, Dennis J. Sweeney, Thomas A. Williams - Anderson, David R. [et.al] (1987)
Descriptive statistic, tabular and graphical approaches, descriptive statistics II, measures of location and dispersion, discrete probability distributions, continuous probability distribution, sambpling and sampling distribuitions, interval estimation, hypothesis testing, statistical inference about means and proportions with two populations, experimental design and analysis of variance, simple linear regression and correlations, multiple regression analysis.